An Approach to Orbital Complications in Rhinosinusitis - Çayır, Serkan; Kayabaşı, Serkan (ENT Updates, 2019)
Objective: Whilst orbital complications arising from acute rhinosinusitis are infrequent in contemporary practice, the spread of infection orbitally or intracranially can result in severe complications and a high mortality. This study aims to review cases of orbital complications arising from rhinosinusitis in the light of the published literature on the topic. Methods: Eight cases of individuals presenting to a particular clinic with the development of orbital complications following sinusitis within the previous four years were included in the study. The characteristic features of these cases in terms of diagnosis, treatment and follow-up were investigated. Results: The mean age of all cases was 29.5 years. In three cases, orbital abscess, and in five cases, preseptal cellulitis, were observed as complications. Both surgical and medical treatment was administered in three cases, while medical treatment alone was used for five cases. Conclusion: The region where the complications of rhinosinusitis are most commonly observed is the orbit, due to its proximity to the paranasal sinuses, especially the ethmoid cells. Where limitation of eye movements, proptosis, and a decrease in vision exists alongside an orbital abscess which itself has developed as a complication of sinusitis, surgical treatment is the most important option to consider to prevent complications.